Disruption of the Circadian Clock Alters Antioxidative Defense via the SIRT1-BMAL1 Pathway in 6-OHDA-Induced Models of Parkinson's Disease. (18th April 2018) - Wang, Yali; Lv, Dongjun; Liu, Wenwen; Li, Siyue; Chen, Jing; Shen, Yun; Wang, Fen; Hu, Li-Fang; Liu, Chun-Feng
Abstract : Parkinson's disease (PD) is the second most common neurodegenerative disease and is known to involve circadian dysfunction and oxidative stress. Although antioxidative defense is regulated by the molecular circadian clock, few studies have examined their function in PD and their regulation by silent information regulator 1 (SIRT1). We hypothesize that reduced antioxidative activity in models of PD results from dysfunction of the molecular circadian clock via the SIRT1 pathway. We treated rats and SH-SY5Y cells with 6-hydroxydopamine (6-OHDA) and measured the expression of core circadian clock and associated nuclear receptor genes using real-time quantitative PCR as well as levels of SIRT1, brain and muscle Arnt-like protein 1 (BMAL1), and acetylated BMAL1 using Western blotting. We found that 6-OHDA treatment altered the expression patterns of clock and antioxidative molecules in vivo and in vitro . We also detected an increased ratio of acetylated BMAL1:BMAL1 and a decreased level of SIRT1. Furthermore, resveratrol, an activator of SIRT1, decreased the acetylation of BMAL1 and inhibited its binding with CRY1, thereby reversing the impaired antioxidative activity induced by 6-OHDA. These results suggest that a dysfunctional circadian clock contributes to an abnormal antioxidative response in PD via a SIRT1-dependent BMAL1 pathway.